HUBUNGAN PEMBERIAN MP-ASI TERLALU DINI DENGAN KEJADIAN DIARE PADA BAYI USIA 0-6 BULAN DI DUSUN 1 SIMPANG 3 KECAMATAN BANDAR BARU KABUPATEN SIBOLANGIT TAHUN 2017 - NURJANNAH . (JURNAL ILMIAH KOHESI, 2019)
Diarrhea is one of the main causes of morbidity and mortality in childhood in developing countries. Diarrhea is caused by various factors, one of which is the administration of MP-ASI that is too early. The purpose of this study is to determine the relationship of ASI (MP-ASI) supplementation with the incidence of diarrhea in infants in Dusun 1 Simpang 3 Village Bandar Baru Subdistrict Sibolangit Regency in 2017 This type of research is analytical research with cross sectional design. The isolation of this study is that all mothers / families of knickknacked babies get MP-ASI and seek treatment at Pustu Dusun 1 Simpang 3, Bandar Baru Subdistrict, Sibolangit Regency in November 2016 - February 2017, taken by purposive simple technique. Bivariate analysis using the chi square test . The results showed that there was a significant relationship between complementary food ASI (MP-ASI) and the incidence of diarrhea in infants with -value 0.006 (<= 0.05). The researcher suggests health workers to improve health services by providing health education regarding the time, frequency, portion, type and method of early MP-ASI administration